An efficient model for robust load frequency control in multi-area power systems with communication delays - Jin, Li; He, Yong; Zhang, Chuan-Ke; Shangguan, Xing-Chen; Jiang, Lin; Wu, Min (Control engineering practice, 2021)
This paper proposes an effective method such that the robust load frequency control (LFC) scheme can be designed efficiently for the large-scale power system with time delay. A novel constraint time-delayed ordinary differential equation (CTODE) model is proposed, based on which a new bounded real lemma (BRL) is established for the H∞ performance analysis. The CTODE model is investigated considering the small number of remote signals influenced by delays in the LFC scheme. It consists of three parts, i.e., a delayed part includes the remote states, whose order is far less than that of the original system and remains unchanged with the increased scale of the power system, and a delay-free (related) part involves the local signals irrelevant (subjected) to the delayed states. Then, the BRL is established by constructing a new Lyapunov functional where the delayed part is employed to address the delay information. Case studies are implemented on the three-area LFC scheme and 39 bus New England systems. Compared with the existing methods, the developed BRL is available for the stability analysis with minor conservatism, but the calculation complexity is greatly reduced in large-scale power systems. Moreover, based on the CTODE model and original model, the robust controllers are designed and compared in robustness against load variations, time delays, and parameter uncertainties. Similar dynamic performance is verified for these two kinds of controllers through robust performance analysis, system eigenvalue analysis, and simulation studies. •An effective method is to design the robust LFC scheme in large-scale systems.•A novel constraint time-delayed ordinary differential equation model is proposed.•A new bounded real lemma is established for the H∞ performance analysis.•Robust controllers are designed efficiently with unreduced dynamic performance.